Sistematika Review: Differentiated Learning Models for Diverse Students in Primary Schools - Arif Hidayat; Ristiyana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
Differentiated instruction has become a central approach in addressing the diverse needs of students in elementary schools. This systematic review aims to identify models of differentiated learning that have been successfully implemented to improve learning outcomes, motivation, and student engagement in the context of Indonesia's elementary schools. Forty journal articles published between 2020 and 2025 were analyzed using a qualitative synthesis approach. The findings indicate that models such as differentiated project-based learning, technology-assisted differentiation, and context-based differentiation are highly effective in catering to various student needs. The study concludes that a combination of collaborative planning and adaptive instruction is essential for sustainable differentiated practices in primary education.